How to … help residents build a personalised memory bank. (2nd August 2019) - Ashurst, Adrian
Abstract : Reminiscing is an enjoyable activity for care home residents and sharing memories with care staff can make it easier for them to deliver person-centred care. Adrian Ashurst talks about the benefits of making a memory bank.